Customer Perceptions Of Modern Technology Integration In The Hospitality Industry - Tomislav (Elektronički Zbornik Radova Veleučilišta u Šibeniku)
The hospitality and tourism industry has changed significantly through the use of modern technologies, both for travellers and service providers. Digitalisation, AI capabilities, IoT, and mobile technologies have enabled a personalised booking, travel, and accommodation experience that provides travellers with timely and useful suggestions, information, and assistance. They have also opened up new opportunities for marketing and customer engagement, providing advanced analytics that enable the hospitality industry to reach a wider audience and deliver tailored offers and services. The objective of this study is to investigate users' attitudes towards the use of modern technologies, their willingness to disclose their private data in order to receive personalised content through digital communication, their perception of the benefits of personalised content, and the impact on their purchase intentions. The influence of gender and level of education on the responses to the survey and the possibility of forming groups in relation to the respondents’ profiles were analysed in more detail. The methods used in this study were a survey, k-means clustering, one-way ANOVA and a two-sample t-test. A questionnaire with 15 statements was used, and 217 responses were collected. User behaviour was segmented using the k-means clustering method, resulting in two homogeneous clusters indicating two main user attitudes. A two sample t-test was conducted to analyse whether there were significant differences between the responses of the different gender groups and between the different education groups. The results showed significant differences in both groups for several questions, as shown in the Results and Discussion section.